Imperceptible sensorics for medical monitoring - Meyer, Marcin; Van Binh, Nguyen; Calero, Venancio; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni); Rogers, John A. (IEEE-NANO 2015 - 15th International Conference on Nanotechnology, 2015)
Society is aging so there is a need for new reliable mobile health monitoring systems. A wireless, stretchable and mobile health monitoring platform has been developed which consists of a wireless stretchable, biocompatible sensor tag placed on the skin and an RFID reader which collects and evaluates data and shows it on a display.
CRIS-Team Scopus Importer:2023-03-20
Keywords: epidermal electronics; medical technologies; mobile devices